2005
DOI: 10.2355/isijinternational.45.1703
|View full text |Cite
|
Sign up to set email alerts
|

Coherent-to-Incoherent Transition of Intergranular bcc-precipitates by Pre-/Post-deformations in a Ni-43Cr Alloy

Abstract: Effects of light deformations before and after precipitation (pre-deformation and post-deformation) on orientation distribution of intergranular bcc-precipitates were examined in a Ni-43mass%Cr alloy by electron backscattered diffraction. It was found that the deviation angles from both the plane/direction parallel orientation relationships in the Kurdjumov-Sachs orientation relationship of intergranular precipitates were increased by both pre-and post-deformations, but post-deformation was more effective. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, we introduce a variant selection rule based on the phenomena that has not been adopted to calculate the transformation textures, although the phenomenon itself has been reported. [8][9][10][11][12] This selection rule has an interesting feature that the texture of parent γ determines the variant selection. Here the selection rule is introduced as a probability function that can be applied to the MODF method.…”
Section: -7)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we introduce a variant selection rule based on the phenomena that has not been adopted to calculate the transformation textures, although the phenomenon itself has been reported. [8][9][10][11][12] This selection rule has an interesting feature that the texture of parent γ determines the variant selection. Here the selection rule is introduced as a probability function that can be applied to the MODF method.…”
Section: -7)mentioning
confidence: 99%
“…In this article, the methods to calculate the transformation textures are briefly reviewed. Then the recent method [5][6][7] that the authors and their co-workers have proposed to predict the transformation texture in hot-rolled steel sheets is described, in which the variant selection [8][9][10][11][12] that we call 'the double KS relation' is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…32,33) Deformation after ferrite nucleation was also reported to effectively aggravate the ferrite orientation relationship with the mother austenite. 34) Figure 7 shows the results of the application of a small load (3 kNϭ26.5 MPa) during the ferrite transformation in a 0.15C-1.4Mn-0.3Si-0.02Ti-0.006B-0.03Al steel.…”
Section: Effect Of Applied Stress On the Ferrite Grain Formationmentioning
confidence: 99%
“…The development of permanent strains during ferrite transformation under an applied stress is well documented in the literature. [36][37][38][39][40] This transformation induced plastic strain can effectively change the orientation relationship of ferrite to the mother austenite, as proposed by Adachi et al 34) Recently, Han et al reported the observation of permanent strain during the recrystallization of ferrite under an applied stress. 41) If plastic strain occurs by interface boundary sliding during the transformation under the applied stress, as suggested by Han 41) or Saotome, 36) the rotation of the ferrite grain orientation during interface boundary sliding is to be expected during the course of the transformation.…”
Section: Effect Of Applied Stress On the Ferrite Grain Formationmentioning
confidence: 99%
“…both coarse and tiny crystals) can be investigated simultaneously, as for example to characterize intergranular precipitation in coarse‐grained materials such as tiny M 23 C 6 carbides in austenitic stainless steels (Hong et al ., 2001; Abdul Wahab & Kral, 2005). Another typical example is variant selection at grain boundaries of the parent phase (Gey & Humbert, 2002; Bhattacharyya et al ., 2003; Banerjee et al ., 2004; Stanford & Bate, 2004; Adachi & Tzusaki, 2005; Adachi et al ., 2005). A way to grain refinement is to enhance intra‐granular nucleation of the new phase by inoculation with well‐suited secondary phases (such as those used for acicular ferrite formation in steel welds).…”
mentioning
confidence: 99%